Entre a igreja e o estado: atribuições e atribulações de um bispo ultramontano na Amazônia (1844-1857) - ANDRADE, Allan Azevedo (Universidade Federal do Pará, 2017)
The present dissertation proposes to analyze the religious-political position of D. José Afonso de Moraes Torres while he was at the head of the diocese of Pará between 1844 and 1857. For that, it is essential to understand his actions and mishaps to administer the spiritual and materially the bishopric , bringing with it the novelty of the ultramontane campaign, at the same time that it was in constant dialogue with the civil power in favor of the Catholic cause.